Einstein, Polanyi, and the Laws of Nature - Jaeger, Lydia (West Conshohocken : Templeton Press, 2012)
What is the relationship between religious belief and the study of nature, between theology and science? This is the fundamental preoccupation of the three different studies brought together in Einstein, Polanyi, and the Laws of Nature.By exploring the highly original yet little known thought of Michael Polanyi, Jaeger highlights the inherent personal investment in any quest for knowledge, including the scientific enterprise, thus raising the question of the objectivity of human knowledge. Considered to be the greatest mind of the twentieth century, Albert Einstein saw scientific research as
Description based upon print version of record.
Keywords: Einstein, Albert, 1879-1955.; Knowledge, Theory of; Polanyi, Michael, 1891-1976.; Religion and science; Religion; Einstein, Albert, -- 1879-1955.; Polanyi, Michael, -- 1891-1976.; Religion and science; Religion; Knowledge, Theory of; RELIGION / Religion & Science; Electronic books